Evaluating Water Productivity and Efficiency in Irrigated Fields Using Remote Sensing: A Case Study in Mozambique’s Sugarcane Cultivation - Pitoro, Valdemiro Simão João [UNESP]; Franco, José Rafael [UNESP]; de Souza Correa, Leonardo Ruan [UNESP]; Manjate, Merlindo Jacinto; Román, Rodrigo Máximo Sánchez [UNESP] (Springer Nature, 2025)
Irrigation plays a vital role in enhancing agricultural production, particularly in sugarcane cultivation. In Mozambique, despite the existence of irrigated areas, inefficient irrigation management remains a challenge. This study aimed to evaluate water productivity in sugarcane cultivation in southern Mozambique using remote sensing data from the Food and Agriculture Organization (FAO) portal to monitor water productivity (WaPOR v2.0 platform). Key variables, including biomass production, evapotranspiration, and precipitation, were analyzed to estimate water productivity. The methodology centered on the relationship between biomass production and evapotranspiration. Evapotranspiration maps demonstrated the effectiveness of center-pivot irrigation in ensuring consistent water response levels throughout the sugarcane growth cycle. Comparative analysis revealed that agricultural productivity and water use efficiency aligned closely with FAO manual recommendations, confirming the feasibility of sustainable cultivation in the areas studied. However, the study faced challenges related to the limited availability of high-resolution data. In underdeveloped regions, agricultural areas are often characterized by a mix of crops rather than large-scale monocultures. The use of freely available lower-resolution images, such as those from the WaPOR platform, may limit the precision of analyses in such contexts, where distinguishing between different crop types is critical. Despite these limitations, the WaPOR v2.0 platform proved to be a valuable alternative for conducting research in data-scarce regions, providing critical insights for improving irrigation planning and promoting the sustainable management of water resources in Mozambique and similar contexts.
Keywords: Irrigation management; WaPOR; Water resource management; Water scarcity